(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Due to a lack of information and the emotional aspect of decision making, many students still do not grasp how to invest effectively and correctly. Students may be drawn to investing by seductive forms of investment that provide significant returns in a relatively short period of time. The goal of this study was to evaluate and analyse the impact of financial literacy on student investment decisions. This research is a descriptive, associative, and comparative study with a quantitative approach in which data is collected, processed, presented, and analysed statistically and descriptively. The study was conducted on students who were not majoring in economics to determine financial literacy obtained during the study year. The survey was administered to individuals with financial literacy knowledge levels of Well literate, Sufficient literate, Less literate, and Not literate. In this study, the purposive sampling strategy was used. Based on the results of SPSS 25 computations, a significance value of 0.000 < 0.05 is known, showing that financial literacy effects student investment decision making.